(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article outlines the main historical aspects and fundamentals of electronic warfare systems of the armed forces as well as important conditions and the factors influencing the formation and functioning of the system.